Lactobacillus helveticus SBT2171 Attenuates Experimental Autoimmune Encephalomyelitis in Mice - Yamashita, Maya; Ukibe, Ken; Matsubara, Yumi; Hosoya, Tomohiro; Sakai, Fumihiko; Kon, Shigeyuki; Arima, Yasunobu; Murakami, Masaaki; Nakagawa, Hisako; Miyazaki, Tadaaki (Frontiers in Microbiology, 2018)
We recently reported that Lactobacillus helveticus SBT2171 (LH2171) inhibited the proliferation and inflammatory cytokine production of primary immune cells in vitro, and alleviated collagen-induced arthritis (CIA) in mice, a model of human rheumatoid arthritis (RA). In this study, we newly investigated whether LH2171 could relieve the severity of experimental autoimmune encephalomyelitis (EAE), a murine model of multiple sclerosis (MS), which is an autoimmune disease, but develop the symptoms by different mechanisms from RA. In MS and EAE, main cause of the disease is the abnormality in CD4+ T cell immunity, whereas in RA and CIA, is that in antibody-mediated immunity. The intraperitoneal administration of LH2171 significantly decreased the incidence and clinical score of EAE in mice. LH2171 also reduced the numbers of pathogenic immune cells, especially Th17 cells, in the spinal cord at the peak stage of disease severity. Interestingly, before the onset of EAE, LH2171 administration remarkably decreased the ratio of Th17 cells to CD4+ T cells in the inguinal lymph nodes (LNs), where pathogenic immune cells are activated to infiltrate the central nervous system, including the spinal cord. Furthermore, the expression of interleukin (IL)-6, an inflammatory cytokine essential for Th17 differentiation, decreased in the LNs of LH2171-administered mice. Moreover, LH2171 significantly inhibited IL-6 production in vitro from both DC2.4 and RAW264.7 cells, model cell lines of antigen-presenting cells. These findings suggest that LH2171 might down-regulate IL-6 production and the subsequent Th17 differentiation and spinal cord infiltration, consequently alleviating EAE symptoms.